Intercomprehension—Interference—Integration. Teaching Polish as a Foreign Language to the Native Speakers of East Slavic Language - Hofmański, Wojciech; Pospiszil-Hofmańska, Karolina (Poznańskie Studia Slawistyczne, 2022)
The paper is an introduction to teaching the Polish language and culture to native users of closely related languages. The presented synthesis is intended for teachers interested in improving their competence in teaching Polish to East Slavs and those who have just started their adventure in Slavic glottodidactics. The paper grew out of a desire to make teaching Polish to East Slavs (mainly Ukrainans) as effective as possible due to the rapidly increasing need because of a large number of war refugees from Ukraine. Based on their experience in teaching Polish to native users of East Slavic languages, the authors pay particular attention to the Slavic intercomprehension phenomenon and its influence on the glottodidactic process. They also address the problem of the key grammatical mismatches and introduce several good practices.